Construction of the Queensferry Crossing and approach roads in Scotland (part 1). Issue 2 (17th December 2018) - Climie, David; Shackman, Lawrence
Abstract : The £1·34 billion Queensferry Crossing over the Firth of Forth in Scotland opened to traffic in 2017. As reported in the authors' 2016 paper in this journal, three design-and-build contracts for the works were awarded in 2011 varying in size from £13 million to £790 million, all under the original project estimates. The crossing opened within 10 weeks of the contract programme and £250 million under budget despite adverse weather conditions. This paper, published in two parts, covers the construction period and the challenges overcome in delivering the largest Scottish infrastructure project in a generation. This first part covers site mobilisation and the foundations, sub-structure and cable-stayed superstructure.